Real-Time Application of Sliding Mode Controller for Coupled Tank Liquid Level System - Abdullah BAŞÇI; Hayriye Tuğba Sekban; Kaan Can (International Journal of Applied Methods in Electronics and Computers, 2016)
In this paper, real time application of a sliding mode control (SMC) is used for level control of experimental setup of liquid level system due to its properties such as robustness against large parameter variation and disturbances rejection. A well-tuned conventional proportional integral (PI) controller is also applied to the two coupled tank system for comparison with the SMC controller. Experimentation of the coupled tank system is realized in two different configurations, namely configuration #1 and configuration #2 respectively. In configuration #1, the water level in the top tank is controlled by a pump. In configuration #2, the water level in the bottom tank is controlled by the water flow coming out of the top tank. The performance of controllers is analysed according to their tracking performance and error elimination capability for different references applied to the system. Experimental results prove that the SMC shows better trajectory tracking performance than PI controller in that the plant transient responses to the desired output changes have shorter settling time and smaller magnitude overshot/undershoot. Robustness of the SMC with respect to water level variation and capability to eliminate external disturbances are also achieved.